2010
DOI: 10.1038/onc.2009.515
|View full text |Cite
|
Sign up to set email alerts
|

Formin-like 2 drives amoeboid invasive cell motility downstream of RhoC

Abstract: Invasive cell migration is a key step for cancer metastasis and involves Rho GTPase-controlled reorganization of the actin cytoskeleton. Altered Rho GTPase expression is found in various malignancies. Particularly, the closely related GTPases RhoA and RhoC are upregulated in many aggressive tumours, but specific effectors that distinguish between these two GTPases to explain mechanistic differences have not been identified. The formins are by far the largest family of Rho GTPase effectors and are characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
151
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(155 citation statements)
references
References 33 publications
4
151
0
Order By: Relevance
“…Importantly, amoeboid motility is highly dependant on extensive reorganization of the actin cytoskeleton (Eichinger et al, 1999;Sahai, 2007;Kitzing et al, 2010). We have shown that elevated Tm5NM1 causes reduced sensitivity to agents that reorganize the actin cytoskeleton (Bryce et al, 2003;Creed et al, 2008), therefore, Tm5NM1 may block the dynamic response of the cytoskeleton that is required to switch to amoeboid type motility.…”
Section: Discussionmentioning
confidence: 97%
“…Importantly, amoeboid motility is highly dependant on extensive reorganization of the actin cytoskeleton (Eichinger et al, 1999;Sahai, 2007;Kitzing et al, 2010). We have shown that elevated Tm5NM1 causes reduced sensitivity to agents that reorganize the actin cytoskeleton (Bryce et al, 2003;Creed et al, 2008), therefore, Tm5NM1 may block the dynamic response of the cytoskeleton that is required to switch to amoeboid type motility.…”
Section: Discussionmentioning
confidence: 97%
“…29) FMNL2 is also autoinhibited and is activated by GTPase RhoC. 30,31) In contrast, FMNL3 has been found to be constitutively active in cells even though its DID and DAD bind to one another in vitro. 29) However, a recent study found that FMNL3, but not FMNL2, is a RhoC-specific target, and is involved in cancer cell invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to a previous screen for the role of formins in cancer cell invasion [28], silencing against all 21 actin nucleators known to be expressed in human non-muscle cells was achieved by transfection with SMARTpool siRNAs consisting of four distinct siRNAs against each target. 96 h post transfection, cells were replated and the frequency of cells with prominent PM blebs quantified.…”
Section: Screening For Actin Nucleators Involved In Pm Blebbingmentioning
confidence: 99%
“…qPCR was performed with 7500 System Software (Applied Biosystems) using Power SYBR Green PCR Master Mix (Applied Biosystems). Primers used for qPCR are summarized in Supplementary information, Figure S9 and were partially validated previously [28]. The DIAPH3 amplicon is between 3154-3255 bp of DIAPH3 Isof3 and is thus present within all putative isoforms except for Isof2.…”
Section: Sirna Knockdownsmentioning
confidence: 99%